MiR‐22, a serum predictor of poor outcome and therapy response in diffuse large B‐cell lymphoma patients. (28th July 2021) - Rinaldi, Federica; Marchesi, Francesco; Palombi, Francesca; Pelosi, Andrea; Di Pace, Anna Laura; Sacconi, Andrea; Terrenato, Irene; Annibali, Ombretta; Tomarchio, Valeria; Marino, Mirella; Cantonetti, Maria; Vaccarini, Sara; et al.
Summary: Diffuse large B‐cell lymphoma (DLBCL) is an aggressive, heterogeneous neoplasm where prognostication and therapeutic decision are challenging. The available prognostic tools are not able to identify all patients refractory to treatment. MicroRNAs, small RNAs frequently deregulated in cancer, stably circulate in biofluids, representing interesting candidates for non‐invasive biomarkers. Here we validated serum miR‐22, an evolutionarily conserved microRNA, as a prognostic/predictive biomarker in DLBCL. Moreover, we found that its expression and release from DLBCL cells are related to therapy response and adversely affect cell proliferation. These results suggest that miR‐22 is a promising complementary or even independent non‐invasive biomarker for DLBCL management.